Is serum ECP level helpful in determining discontinuation of inhaled corticosteroid therapy in asthmatic children? - (:unkn) unknown (My University, 2000)
BACKGROUND: Serum eosinophil cationic protein (ECP) has been promoted as a direct marker of eosinophilic inflammation of the airways in patients with asthma. However, its role in monitoring disease activity and management of inhaled corticosteroid (ICS) therapy is not well defined. METHODS: We determined serum ECP (s-ECP) levels in 95 children (mean +/- SD age, 6.2 +/- 3.9 years) with asthma. At the time of measurements, 34 out of 95 children were symptomatic whereas 61 were in stable condition; and 56 of 95 patients were on maintenance ICS therapy. ICS prophylaxis was withdrawn in 16 of those 56 patients who remained asymptomatic with a dose of 100 micrograms/day of budesonide for 8 weeks. Eight out of these 16 children had to restart ICS therapy within the following 12 weeks, while the remaining 8 children continued to be asymptomatic within the same period. RESULTS: ECP values and number of patients with a high ECP level (> or = 15 micrograms/L) were significantly higher in the symptomatic group (p = 0.01 and p = 0.006, respectively). Also, ECP levels were significantly lower in the group who achieved clinical remission (n = 16) in which ICS therapy was withdrawn when compared with those who needed to continue ICS prophylaxis. On the other hand, no difference was observed in the comparison of the ECP levels of children who had to restart ICS therapy and those who did not. CONCLUSION: Our results suggest that, although the determination of s-ECP levels are in accordance with clinical evaluation of disease activity, it is not useful in determining discontinuation of ICS therapy.
Keywords: Female; Humans; Glucocorticoids; Adolescent; Infant; Male; Biomarkers; Blood Proteins; Child; Child, Preschool; Administration, Topical; Anti-Inflammatory Agents; Asthma; Budesonide; Anti-Asthmatic Agents; Eosinophil Granule Proteins; Ribonucleases